2021
DOI: 10.3390/su131910493
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Technical–Tactical Categorisation in Taekwondo: From General Tactical Objectives to Combat Situations

Abstract: Taekwondo competition underwent enormous development with the recent introduction of electronic scoring devices and rule changes. Although the competitive model of taekwondo had been previously studied, most of the literature that analyses this model was previous to the introduction of electronic devices or not based on a prior system of categories. Not only are results of an up-to-date taxonomy essential to guarantee the sustainability of future research about taekwondo based on methodological observation, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In dual-contest sports, the importance of color for referees is not limited to making the right calls. Actually, color provides support in the crucial task of scoring attribution, helping referees to visually differentiate the short duration, high intensity, and often simultaneous techniques [ 3 ] performed by the two athletes. In this context, Hagemann et al [ 4 ] hypothesized the presence of a psychological effect in referees triggered by the perception of colors that could lead to biases in the evaluation of identical performances.…”
Section: Introductionmentioning
confidence: 99%
“…In dual-contest sports, the importance of color for referees is not limited to making the right calls. Actually, color provides support in the crucial task of scoring attribution, helping referees to visually differentiate the short duration, high intensity, and often simultaneous techniques [ 3 ] performed by the two athletes. In this context, Hagemann et al [ 4 ] hypothesized the presence of a psychological effect in referees triggered by the perception of colors that could lead to biases in the evaluation of identical performances.…”
Section: Introductionmentioning
confidence: 99%
“…The results (Table 3) confirm the reliability of the evaluators for both group (women and men). The women's group results presented for intra-rater reliability (evaluator 1 vs. evaluator 1) were excellent with 0.956 (p < 0.01) lower than Sousa et al, [6] who presented 0.994 (p < 0.05) with almost perfect conformity and Barrientos et al with ICC = 0.99 that revealed excellent to perfect results [33]. The inter-rater results, among the expert evaluators, presented good values of more than 0.800 (p < 0.01) once again, lower than Sousa et al, who reported 0.968 (p < 0.05) [6].…”
Section: Discussionmentioning
confidence: 57%
“…Since the establishment of the World Taekwondo Federation (WTF) in 1973, the competition rules of Taekwondo have been revised more than 40 times [6]. In competitions conducted according to the pre-2015 rules, Taekwondo athletes did not generally apply difficult technical approaches, but preferred to use secure frontal skills to win the game [7], which is why the roundhouse kick was the most popular means of scoring [8].…”
Section: Introductionmentioning
confidence: 99%